2020
DOI: 10.1136/bmjdrc-2019-001025
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon receptor antagonist upregulates circulating GLP-1 level by promoting intestinal L-cell proliferation and GLP-1 production in type 2 diabetes

Abstract: ObjectiveGlucagon receptor (GCGR) blockage improves glycemic control and increases circulating glucagon-like peptide-1 (GLP-1) level in diabetic animals and humans. The elevated GLP-1 has been reported to be involved in the hypoglycemic effect of GCGR blockage. However, the source of this elevation remains to be clarified.Research design and methodsREMD 2.59, a human GCGR monoclonal antibody (mAb), was administrated for 12 weeks in db/db mice and high-fat diet+streptozotocin (HFD/STZ)-induced type 2 diabetic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…It further suggested the rapid proliferation state of endothelial cells when QKI-7 was highly expressed, and the results of CCK-8 finally showed that the overexpression of QKI-7 led to a significant increase in cell proliferation efficiency. It showed that QKI-7 overexpression had a remarkable stimulating effect on endothelial cell development, which was also consistent with the endothelial cell proliferation observed in patients with diabetes and atherosclerosis in the clinic [ 33 ]. In further research, we also found that after knocking down the QKI-7 expression level in hiPSC by siRNA, the expression levels of key endothelial cell genes CD144, NLGN1, and TSG6 were significantly increased; the expression of endothelial cell proliferation-related cytokine TNF - α , IL-1 β , IFN- γ , and PGI2 also decreased; the proliferation efficiency of endothelial cells was significantly reduced.…”
Section: Discussionsupporting
confidence: 76%
“…It further suggested the rapid proliferation state of endothelial cells when QKI-7 was highly expressed, and the results of CCK-8 finally showed that the overexpression of QKI-7 led to a significant increase in cell proliferation efficiency. It showed that QKI-7 overexpression had a remarkable stimulating effect on endothelial cell development, which was also consistent with the endothelial cell proliferation observed in patients with diabetes and atherosclerosis in the clinic [ 33 ]. In further research, we also found that after knocking down the QKI-7 expression level in hiPSC by siRNA, the expression levels of key endothelial cell genes CD144, NLGN1, and TSG6 were significantly increased; the expression of endothelial cell proliferation-related cytokine TNF - α , IL-1 β , IFN- γ , and PGI2 also decreased; the proliferation efficiency of endothelial cells was significantly reduced.…”
Section: Discussionsupporting
confidence: 76%
“…The most relevant aspect is the complex and unexploited network of interactions between pancreatic and gut hormones. The model proposed by Unger and Lee [7,8] consisting in an increase of GLP-1 circulating levels by glucagon receptor blocking, was confirmed later by other experimental data [14,15]. Interesting information was provided by an in vivo mouse model in which both the action of glucagon and that of GLP-1 was inhibited.…”
Section: Gastrointestinal Hormone Networkmentioning
confidence: 80%
“…According to this report, glucagon secretion in the intestine is part of normal physiology, and not a compensatory mechanism for disrupted pancreatic secretion, since all donors in the study had a healthy pancreas. Another recent study revealed a paracrine modulation of GCGR in L-cells, since GCGR antagonism increases the L-cell population [ 38 ].…”
Section: Discussionmentioning
confidence: 99%